Local governance in developing countries - Shah, Anwar (Public sector governance and accountability series., 2006)
This book provides a new institutional economics perspective on alternative models of local governance, offering a comprehensive view of local government organization and finance in the developing world. The experiences of ten developing/transition economies are reviewed to draw lessons of general interest in strengthening responsive, responsible, and accountable local governance. The book is written in simple user friendly language to facilitate a wider readership by policy makers and practitioners in addition to students and scholars of public finance, economics and politics.